Lecturers’ Work Performance of Islamic Education - Zulvia Trinova; Remiswal Remiswal; Nini Nini; Alfurqan Alfurqan (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
Many problems were found in the field related to lecturers. Lecturers who are supposed to be disciplined come to class to teach, but some come late to class and end class early before the time runs out. There are lecturers who come and fill out the attendance list at the picket and go straight to class to teach, but there are also those who are not in class to teach because they have other purposes. Some senior lecturers ask their juniors or teaching assistants to teach classes. Some lecturers conduct proposal seminars, comprehensive examinations or conduct counseling for students as academic advisers, or provide student thesis guidance. In the learning process, the approach taken to students sometimes does not have a positive effect on them, the learning methods used are also less varied. The purpose of this study was to obtain an overview and contribution given by the work situation and achievement motivation to lecturer performance. This research is descriptive quantitative. The main data were obtained from observations, questionnaires, interviews, and documentation. Sources of data in this study are lecturers of the Department of Islamic Religious Education and several students. Researchers performed qualitative data analysis by means of data reduction, categorization, and data verification, so that it can be concluded from the data obtained. Based on the results and discussion, it can be concluded that the work situation and individual achievement motivation affect the work performance of the lecturers of the Islamic Education Department, Tarbiyah and Teacher Training Department, UIN Imam Bonjol Padang. The learning approaches used are expository, inquiry, emotional, PAKEM approach and andragogy. The learning method applied is multi-method in the form of active learning. The media used are lecturers of Islamic Religious Education, both printed media in the form of discussion papers and electronic media.